Simulation of Transmission Spectra to Characterize Atmosphere of Exoplanets - Robiatul Muztaba; Fera Gustina Purwati; Taufiq Hidayat (Journal of Multidisciplinary Academic, 2018)
Today, more than three thousand exoplanets have been confirmed and other millions waiting to be discovered. In addition to determine their physical and precise orbital parameters of exoplanets atmosphere is of important to characterize. This will allows us to investigate their evolution and eventually to see the possibility for some exoplanets to harbor a living system. By using the TAU code, we undertake simulations of exoplanets transmission spectra in the near infrared in order to retrieve transmission spectral profiles of these exoplanets. The simulations adopted thermal profile as well as absorption cross-section as a wavelength function for each modeled absorber or trace molecule H2O (0.24 – 0.34 microns) and C2H6 (0-20 microns). The computation provide scale height, optical depth, transit depth and absorption spectra of absorber. The peak of the spectra may lead us to determine the abundance of each molecule in the atmosphere. Our result gave scale height 89% compared to existing data, and total number density of H2O is 5.42×1025 m-3 for Jupiter's atmosphere. Subsequently, we make spectral models of some hot Jupiters, including HD 189733b with WASP 12b, and earth-like exoplanets.